The effect of a levonorgestrel-releasing intrauterine device on ovariectomized rat endometrium under estrogen replacement therapy - (:unkn) unknown (My University, 2004)
Objective: Our aim was to investigate the effects of levonorgestrel- releasing intrauterine system on the endometrium of ovariectomized rats under estrogen replacement therapy. Methods: Twenty-four Sprague-Dawley rats were divided into four groups and operated for the insertion of levonorgestrel- releasing (3 μg/day) or placebo-bearing intrauterine devices (IUD). Following the operation, the rats were randomly assigned to take estrogen (0.01 mg. per kg. rats) or placebo replacement therapy for 30 days. Endometrial biopsies were collected at the end of the study period. The sampled endometrial tissues have been analyzed for morphologic criteria under the light microscope. Group I was assigned to take levonorgestrel-releasing IUD and systemic estrogen whereas Group II was assigned for levonorgestrel-releasing IUD and systemic placebo and Group III for placebo-bearing IUD and systemic estrogen; finally Group IV was treated with placebo-bearing IUD and systemic placebo. Results: The endometrial morphology of Group I revealed inactive endometrium in 50%, edema in 33% and atrophy in 16% whereas the endometrial morphology of Group II revealed inactive endometrium in 66%, and atrophy in 33%. The endometrial morphology of Group III revealed epithelial hyperplasia in 66%, edema in 16% and myometrial hyperplasia in 16% while inactive endometrium was identified in 16%, and atrophy in 83% of rats in Group IV. Conclusion: Our results revealed that progestagen containing intrauterine systems are sufficient enough to protect the endometrium from hyperplasia in rats under systemic estrogen replacement therapy. This is somehow encouraging data to support that the endometrium of postmenopausal women under systemic estrogen can be sufficiently protected by an intrauterine gestagen-containing device. The use of such an IUD will serve to protect them from the adverse effects of systemic gestagens.
Keywords: Estrogen replacement therapy; Intrauterine device; Levonorgestrel; Rat endometrium